Analisis Kepuasan Kerja terhadap Kinerja Karyawan Pada Bank 9 Jambi Cabang Muara Bulian - Endang Meiliani; Sopian Sopian (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
This study aims to analyze the variable job satisfaction on employee performance at Bank 9 Jambi Muara Bulian Branch. This study uses a sample of 41 employees who work at Bank 9 Jambi Muara Bulian Branch. The analytical method in this research is descriptive qualitative and quantitative methodsFor the t-test where (tcount> ttable) the job satisfaction variable in this study shows a value of (4,418>1,68595) meaning that the job satisfaction variable has a significant effect on employee performance variables. As for the f test where Fcount > Ftable with a value of (158.085>3.24). it means that simultaneously the job satisfaction variable has a significant effect on employee performance at Bank 9 Jambi Muara Bulian Branch and the Adjusted R Square value is 0.887. It means that the percentage of job satisfaction on employee performance is 88.7% and 0.113 or 11.3% is influenced by other variables